2020
DOI: 10.1002/jnr.24684
|View full text |Cite
|
Sign up to set email alerts
|

Degron capability of the hydrophobic C‐terminus of the polyglutamine disease protein, ataxin‐3

Abstract: Ataxin‐3 is a deubiquitinase and polyglutamine disease protein whose cellular properties and functions are not entirely understood. Mutations in ataxin‐3 cause spinocerebellar ataxia type 3 (SCA3), a neurodegenerative disorder that is a member of the polyglutamine family of diseases. Two major isoforms arise from alternative splicing of ATXN3 and are differently toxic in vivo as a result of faster proteasomal degradation of one isoform compared to the other. The isoforms vary only at their C‐termini, suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 66 publications
1
11
1
Order By: Relevance
“…Atxn3(Q80) cDNA sequence was based on the human ATXN3 sequences used in previous publications (Winborn et al, 2008;Todi et al, 2009Todi et al, , 2010Harris et al, 2010;Nicastro et al, 2010;Blount et al, 2014Blount et al, , 2020Tsou et al, 2015b;Costa et al, 2016;Sutton et al, 2017;Ristic et al, 2018;Johnson et al, 2019Johnson et al, , 2020Johnson et al, , 2021Johnson et al, , 2022a. The mutagenesis of Atxn3(Q80)-UbS1 * , Atxn3(Q80)-C14 * -UbS1 * and Atxn3(Q80)-UbS1 * -UIM * were carried out by Genscript 1 .…”
Section: Plasmid Designmentioning
confidence: 99%
See 3 more Smart Citations
“…Atxn3(Q80) cDNA sequence was based on the human ATXN3 sequences used in previous publications (Winborn et al, 2008;Todi et al, 2009Todi et al, , 2010Harris et al, 2010;Nicastro et al, 2010;Blount et al, 2014Blount et al, , 2020Tsou et al, 2015b;Costa et al, 2016;Sutton et al, 2017;Ristic et al, 2018;Johnson et al, 2019Johnson et al, , 2020Johnson et al, , 2021Johnson et al, , 2022a. The mutagenesis of Atxn3(Q80)-UbS1 * , Atxn3(Q80)-C14 * -UbS1 * and Atxn3(Q80)-UbS1 * -UIM * were carried out by Genscript 1 .…”
Section: Plasmid Designmentioning
confidence: 99%
“…All flies were heterozygous for driver and transgene(s). All transgenic Atxn3 lines used here were generated by us and were reported previously (Tsou et al, 2013(Tsou et al, , 2015bSutton et al, 2017;Johnson et al, 2019Johnson et al, , 2020Johnson et al, , 2022aBlount et al, 2020) or are being reported here for the first time, as noted in the results section and figure legends. All crosses were conducted at 25 • C in diurnal environments with 12 h light/dark cycles and on conventional cornmeal media.…”
Section: Drosophila Husbandrymentioning
confidence: 99%
See 2 more Smart Citations
“…(This isoform was the originally cloned version of ATXN3 .) The alternative isoform is no less toxic than the predominant version in fly models of SCA3, but it is present at markedly lower protein levels because of enhanced proteasomal degradation due to its C-terminus serving as a degron sequence ( Johnson et al, 2019 ; Blount et al, 2020 ).…”
Section: Polyq Diseases and Protein Contextmentioning
confidence: 99%